Evolutionary history and diversity in the ball roller beetle Canthon cyanellus - Nolasco-Soto, Janet; González-Astorga, Jorge; Espinosa de los Monteros, Alejandro; Favila, Mario E. (Frontiers in Ecology and Evolution, 2023)
To understand the evolutionary history of species, it is necessary to know the mechanisms for reproductive isolation, divergence-time between populations, and the relative action of the evolutionary forces (e.g., mutation, genetic drift, gene flow) within and between populations of the same, or closely related species. Although Canthon is one of the more diverse genera of neotropical beetles, insufficient research has been done to comprehend the divergent patterns that explain its speciation process. The absence of diagnostic morphological characters and the wide geographic variation of qualitative traits in Scarabaeinae obscures species delimitation, genealogical limits between populations, and its taxonomy. Canthon cyanellus is one of the best-known species in ecological and evolutionary aspects. It is a widely distributed species in the tropical forests of America. Also, the current deforestation has facilitated its incursion into open areas. Individuals from different populations have similar morphological characters but show wide variation in body color throughout their distribution, which makes it difficult to delimit the subspecies that comprise it. Recently, studies have been carried out to elucidate the pre-and postzygotic isolation mechanisms between populations and the historical biogeographical processes favoring cladogenesis events during the Pleistocene. Morphological variation of the male genitalia does not correspond to the phylogeographic structure. However, the morphological differences in one of the pieces of the endophallic sclerites have allowed a preliminary delimitation of some genetically differentiated clades. Finally, we consider that the joint analysis of traditional morphological taxonomy and phylogeography is important to understand the speciation process in the C. cyanellus complex.